USM ACADEMICIAN BAGS DOCTORAL DISSERTATION AWARD RUNNER-UP PRIZE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 3 May 2017 – A dissertation submitted by an academician from the Universiti Sains Malaysia (USM) School of Computer Sciences has been chosen as runnerup in a recentlyheld international information competition.